1975
DOI: 10.2307/3897223
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Related to Medusahead Distribution

Abstract: Sites particularly susceptible to medusahead invasion in the more arid portions of Idaho were either those with well-developed soil profiles, particularly those with high clay content either at or near the surface; or those occupying topographic positions that received additional runoff from adjacent sites. In more mesic climates moderately well developed soils appeared as highly susceptible as the well-developed soils. Conversely, soils with little profile development, particularly those which were well drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 8 publications
3
20
0
Order By: Relevance
“…Our data support observations and suggestions that medusahead is a highly competitive plant (Davies and Svejcar 2008;Young 1992;Young and Mangold 2008), capable of expanding its current range (Dahl and Tisdale 1975;Johnson and Davies 2012;Young 1992). Establishment of medusahead was slightly but significantly higher on the sandy loam, but it was high in all treatments (ranging from 83 to 93%; Figure 2a).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data support observations and suggestions that medusahead is a highly competitive plant (Davies and Svejcar 2008;Young 1992;Young and Mangold 2008), capable of expanding its current range (Dahl and Tisdale 1975;Johnson and Davies 2012;Young 1992). Establishment of medusahead was slightly but significantly higher on the sandy loam, but it was high in all treatments (ranging from 83 to 93%; Figure 2a).…”
Section: Discussionsupporting
confidence: 90%
“…It appears that medusahead invasion is most closely associated with fine-textured to moderately fine-textured soils, including clays and clay loams (Dahl and Tisdale 1975;Young and Evans 1970), which may be related to differences in water holding capacity. However, limited observations have suggested that medusahead is capable of expanding its current range into more coarse-textured soils (Dahl and Tisdale 1975;Young 1992), demonstrating the need for restoration studies that compare plant performance in different soil types.…”
mentioning
confidence: 99%
“…These communities include low sagebrush and mountain big sagebrush communities as well as some Wyoming big sagebrush communities. One common feature among these communities is the presence of a clay horizon in the soil (Dahl and Tisdale 1975).…”
Section: Annual Grassesmentioning
confidence: 99%
“…It spread rapidly in the 1930s (Young and Evans 1982) and has become a major invasive species across millions of hectares on clayrich, arid to semi-arid rangelands of the western United States (Young and Evans 1970;Dahl and Tisdale 1975). Taeniatherum caput-medusae, like the invasive annual grass Bromus tectorum L., increases the risk and scale of catastrophic wildfires (D' Antonio and Vitousek 1992).…”
Section: Introductionmentioning
confidence: 99%